2021
DOI: 10.1155/2021/5574176
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Prognostic Value of MEX3A and Its Relationship with Immune Infiltrates in Ovarian Cancer

Abstract: MEX3A is a critical RNA-binding ubiquitin ligase that is upregulated in various types of cancer. However, the correlations of MEX3A with prognosis and its molecular mechanism in ovarian cancer (OC) remain unclear. The expression level, prognostic values, and the genetic variations of MEX3A were analyzed via Gene Expression Profiling Interactive Analysis (GEPIA) Oncomine, Kaplan–Meier plotter, and cBioPortal. We used the LinkedOmics database to investigate the functions of MEX3A coexpressed genes and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…63 LAMTOR2 has strong interaction with the expression of the MEX3A, which owns prognostic value in ovarian cancer. 64 With the help of the signature, each LGG sample could be identified by its own risk level. In addition, we found that high-risk LGG patients had poor prognosis, upregulated infiltration of neutrophil, macrophage (M1 and M2), Treg, and myeloid dendritic cell, downregulated infiltration of monocyte and NK cell, and increased expression of large number of ICG genes.…”
Section: Discussionmentioning
confidence: 99%
“…63 LAMTOR2 has strong interaction with the expression of the MEX3A, which owns prognostic value in ovarian cancer. 64 With the help of the signature, each LGG sample could be identified by its own risk level. In addition, we found that high-risk LGG patients had poor prognosis, upregulated infiltration of neutrophil, macrophage (M1 and M2), Treg, and myeloid dendritic cell, downregulated infiltration of monocyte and NK cell, and increased expression of large number of ICG genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that MEX3A is highly expressed in a variety of cancers and promotes the occurrence and metastasis of cancer, which is related to the poor prognosis of patients [ 27 29 ]. MEX3A might regulate immune infiltration in the microenvironment of ovarian cancer cells and is a potential therapeutic target [ 30 ]. However, MEX3A was reported to suppress proliferation and EMT by restraining the Akt signaling pathway in cervical cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because SMYD2 usually upregulates gene expression by mediating the H3K36 methylation, we therefore, explored genes showing positive correlation with SMYD2 and obtained that SMYD2 activated MEX3A expression by promoting H3K36me2 modification on its promoter. MEX3A has been reported as a tumour promoter in several human cancers, [35][36][37][38] or as a tumour suppressor in cervical cancer. 39 The different roles might be owing to the different targets it affects.…”
Section: Discussionmentioning
confidence: 99%